2009
DOI: 10.1111/j.1610-0387.2009.07041.x
|View full text |Cite
|
Sign up to set email alerts
|

Progress of multiple cutaneous and subcutaneous melanoma metastases of the face during imiquimod treatment

Abstract: A 68-year-old man developed a local recurrence with multiple cutaneous and subcutaneous nodules three months after excision of a primary malignant melanoma of the temple. Despite extensive surgery and adjuvant irradiation, another local recurrence occurred. Following further local progression during dacarbazine chemotherapy, topical treatment with imiquimod was begun and the chemotherapy was changed to fotemustine. During this treatment further local progression occurred and two months later regional lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Twenty‐three reports were published on the use of imiquimod on metastatic melanoma involving 55 patients (Table S2). In the 23 reports on 55 patients with metastatic melanoma, most of the treated metastatic lesions showed complete or partial responses, but one case report showed continued progression of disease that resulted in patient death . Miller and colleagues showed that the liver and iliac fossa metastases of one patient with metastatic melanoma responded to imiquimod applied to the abdomen and pelvis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐three reports were published on the use of imiquimod on metastatic melanoma involving 55 patients (Table S2). In the 23 reports on 55 patients with metastatic melanoma, most of the treated metastatic lesions showed complete or partial responses, but one case report showed continued progression of disease that resulted in patient death . Miller and colleagues showed that the liver and iliac fossa metastases of one patient with metastatic melanoma responded to imiquimod applied to the abdomen and pelvis .…”
Section: Discussionmentioning
confidence: 99%
“…Similar heterogeneity exists among these studies, including the treatment regimen, length of treatment, and follow‐up times (Table S2). Given the difficulties with treatment of metastatic melanoma, the treatment regimens involved more combination therapies, such as combining imiquimod with chemotherapy, IL‐2, TNF‐α 2b, GM‐CSF, pulsed dye laser, 5‐fluorouracil, retinoids, in situ photoimmunotherapy, and radiation therapy . Overall, despite a lack of randomized controlled trials, it appears that imiquimod could be used as a palliative treatment for melanoma metastases when other options are not effective or feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A partial response (PR) has been observed in five patients (17.9%) and in two of them the residual local disease was surgically excised at the end of the treatment. 52 A local disease progression (Figure 4) has been detected in three cases (10.7%): in two cases the lesions were located on face and scalp area 62,64 and both patients died of melanoma visceral spreading.…”
Section: The Use Of Topical Imiquimod In Cutaneous Melanoma Metastasesmentioning
confidence: 99%
“…In five cases (18%), local imiquimod was performed as first line treatment without any previous systemic or local medications. 37,51,53,60,66 In 16 reports (58%) topical imiquimod application followed or was concomitant to systemic treatments: dacarbazine, 10,62 dacarbazine plus IFNα, 52,56 IFNα alone as adjuvant 53,56,57,64 , and ipilimumab. 65 In three cases, imiquimod was applied locally during a trial in a patient assuming MM peptide vaccine.…”
Section: The Use Of Topical Imiquimod In Cutaneous Melanoma Metastasesmentioning
confidence: 99%